Analisis kesalahan peserta didik berdasarkan teori kastolan dalam menyelesaikan soal higher order thinking skills (HOTS) ditinjau dari self-efficacy - Aep Saepuloh; Nani Ratnaningsih; Eko Yulianto (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2026)
Research on self-efficacy mostly examines its relationship with mathematical ability without linking it to errors in solving HOTS questions. This condition shows that there is a research gap related to error analysis based on Kastolan Theory in terms of self-efficacy. This research aims to analyze students' errors in solving HOTS statistics questions based on Kastolan Theory in terms of self-efficacy. The research used a descriptive qualitative approach with subjects of four class VIII  students consisting of two students with high self-efficacy and two students with low self-efficacy. Data was collected through questionnaires, HOTS tests, interviews and documentation. The research results showed that students with high and low self-efficacy made conceptual, procedural and technical errors. However, low self-efficacy students show more basic errors than high self-efficacy students. Conceptual errors are the most dominant errors. This research contributes to expanding the study of error analysis based on Kastolan Theory by revealing the characteristics of errors based on the level of self-efficacy, so that it can become a basis for designing learning that suits students' needs.